Coincidental TID Production by Tropospheric Weather During the August 2017 Total Solar Eclipse. Issue 20 (25th October 2018) - Mrak, Sebastijan; Semeter, Joshua; Nishimura, Y.; Hirsch, Michael; Sivadas, Nithin
Abstract: It has been proposed (Chimonas & Hines, 1970, https://doi.org/10.1029/JA075i004p00875) that a total solar eclipse should generate internal gravity waves (GWs) that manifest as traveling ionospheric disturbances (TIDs) at ionospheric heights. Zhang et al. (2017, https://doi.org/10.1002/2017GL076054) recently reported observations of electron density perturbations trailing the region of maximum obscuration, claiming the results as the first unambiguous evidences for eclipse‐induced bow waves. We present evidence showing extensive TID activity on two consecutive days, the day of the eclipse and the day before. A particularly intense TID concentric wavefield emerged from the background ionosphere 5 hr before the arrival of the totality and persisted there throughout the eclipse. The apparent center was located over Iowa/South Dakota region, 300–500 km north from the eclipse path. We examine concurrent observations of tropospheric and ionospheric weather and find a great spatiotemporal correlation. TID wave parameters do agree with previous observations and models of thunderstorm‐generated GWs/TIDs; conversely, the wave parameters are an order of magnitude off from modeling results for eclipse‐generated GWs/TIDs. Plain Language Summary: Recent studies of ionospheric dynamics on the day of the 2017 total solar eclipse observed concentric waves in the ionosphere and attributed them to the eclipse itself. We present a concurrent analysis of ionospheric and tropospheric weather and find a strong correlation between thunderstorm activity and the ionospheric wavefield. We find that the ionospheric waves emerged 5 hr before the eclipse and they persisted within a confined region of space throughout the end of the eclipse. A careful analysis of these waves shows remarkable agreement with previous studies of tropospheric weather‐generated gravity waves and their imprint in the ionosphere as traveling ionospheric disturbances . Further comparison with models and other recent observations of the 2017 total solar eclipse further supports our conclusions to ascribe the ionospheric wavefield to the tropospheric weather as the driving mechanism. In aggregate, the ionosphere on the day of the eclipse provided us with an intriguing pattern, showing simultaneous forcing from the Sun and from the troposphere. Key Points: The TIDs previously ascribed to the 2017 total solar eclipse are not associated with the eclipse; they were present at other times The TID pattern, speed, and wavelength are inconsistent with the bow‐wave hypothesis; evidence is presented, suggesting a thunderstorm origin The TIDs with a concentric pattern propagated radially away from the point source in the east/southeast direction